Phenotypic plasticity in benthic diatoms: cellular motility and photoacclimation capacity - Bastos, Alexandra Oliveira (2022)
Phenotypic plasticity is the capacity of organisms with the same genome to exhibit different characteristics under diverse environmental conditions, being therefore considered an adaptation strategy for surviving in variable environments. One type of phenotypic plasticity is photoacclimation, which consists in phenotypical changes caused by the changes in growth light conditions. Benthic diatoms are microalgae that inhabit estuaries, which are very heterogeneous and variable environments. Some diatom growth forms (motile epipelic diatoms; EPL) can avoid the drastic light changes they might experience in their natural habitat by using cellular motility and vertical migration in the sediment, while others do not have that behavioral photoprotective mechanism (non-motile epipsammic diatoms; EPM). This study addressed the characterization of the patterns of photoacclimation in EPL and EPM diatom species and tested the hypothesis that EPM species have a larger capacity to photoacclimate to different growth light conditions than EPL ones. Two experiments were carried out. First, an experiment for analyzing the steady state photoacclimation of cultures and characterize the range of variation between long term acclimation to high (HL) and low (LL) light conditions. A second experiment was carried out to quantify the magnitude and rate of short-term acclimation of different species of diatoms to a change in growth light. The parameters Fv/Fm (maximum quantum yield of photosystem II), Chl a per cell, and the photoacclimation parameter Ek were chosen as the best parameters to characterize the acclimation state of the cultures. EPM diatoms showed a higher variation between LL and HL in four of the six analyzed photophysiological parameters (Fv/Fm, Chl a per cell, rETRm and Ek), supporting the hypothesis of the study. The short-term experiment showed a larger phenotypic variation in EPL than in EPM species. Because one of the experiments focused on the acclimation capacity and the other more on the rate of acclimation, the results obtained in the first experiment do not invalidate the results obtained in the second. The results show that there seems to be a higher photoacclimation capacity in EPM species, but that EPL species seem to be faster to acclimate to new light conditions.